Evaluation of Physical Education Online Learning Based on Technological Pedagogical Content Knowledge for Students of Junior High School 1 Gondang Jawa Timur - Pratama, Arga Cahya; Soegiyanto, Soegiyanto; Priyono, Bambang (Journal of Physical Education and Sports, 2021)
The obstacles to online physical education learning at Junior High School 1 Gondang drove this research. This is a qualitative study with a stake evaluation methodology that was examined at the Antecedent, Transaction, and Outcome stages. When the study was conducted at SMPN 1 Gondang in the Nganjuk Regency. Physical Education (PE) teachers, school principals, and junior high school students in grades VII, VIII, and IX of SMPN 1 Gondang served as data sources for study. Techniques for data collection was observation, interviewing, and documenting. Data analysis was composed of four interacting components: data collection, data reduction, data display, and conclusion. The of this research Antecendent were implemented in the form of distance learning since mid-March 2020 with virtual. Access to the internet network is a similar barrier that teachers and students experience. By modifying learning settings during the covid 19 pandemic, physical education learning device transactions are made per lesson indicator. Google form, wa group, youtube, zoom, and achievement applications were all used as media. The outcomes / learning outcomes of physical and social education students during the covid 19 pandemic were assessed by the examination of assignments and tests. Students achieved results above the Minimum Completeness Criteria. The research concludes that online physical education learning at SMP N 1 Gondang is progressing well, despite certain obstacles, and should be used as evaluation material for physical education online learning during the covid 19 pandemic to make it even better.